Bibliometric Analysis of Circular Agriculture - Loso Judijanto (West Science Agro, 2026)
Circular agriculture has become a significant research area where scholars explore ways to implement circular economy concepts in agriculture and promote resource efficiency, waste valorization, and sustainable food production. In this work, an attempt is made to analyze the evolution, intellectual structure, collaborative practices, and current research trends of circular agriculture publications through the application of a bibliometric approach. To achieve the stated objectives, the data collection process was conducted through the use of Scopus and relevant keywords concerning the area of interest, while VOSviewer software was employed to conduct citation analysis, co-authorship analysis, country and institutional collaboration mapping, keyword co-occurrence analysis, overlay visualization, and density analysis. It was revealed that the research area of circular agriculture had undergone a significant development and is strongly associated with such areas as circular economy, sustainability, bioeconomy, agricultural waste management, nutrient recycling, and resource recovery. Through the citation analysis, the most influential papers were found to be centered around topics such as transformation of agricultural supply chain, waste valorization, circular bioeconomy, and sustainable resource management. Collaboration analysis showed that there is a high level of international collaboration in the field of interest, while the key countries making their contributions to the development of circular agriculture include China, the USA, and several European countries. Through the analysis of keywords, it could be said that three key research dimensions are currently dominating in the field, namely circular resource management, sustainable agricultural transformation, and technological innovations in agriculture. Current research trends indicate growing interest towards bio-based solutions, circular supply chains, digital agriculture, and sustainable food systems.